What Promises Does the Eurasian Customs Union Hold for the Future? - Carneiro, Francisco G. (World Bank, Washington, DC, 2014)
Established in 2010, the Eurasian Customs Union (ECU) carries significant economic weight as three of its member countries represent a potentially large consumer market. Drawing on existing literature that has studied the likely impacts of the ECU in Central Asia, this note discusses the ECU's pitfalls and potential benefits. After briefly describing the main features of the ECU, this note assesses whether the changes introduced after its establishment have benefitted all of its members equally, and concludes with a discussion of what will need to change to achieve the ECU's full potential. Available evidence suggests that the Russian Federation has been the main beneficiary in the short term, but that there are several benefits to be gained by other members in the medium to long term. Full realization of these benefits, however, will require political commitment and steadfast action to reduce nontariff barriers (NTBs), improve trade facilitation, and reduce the costs of trading across borders in the region.